Bioremediation of leachate from landfills in Selangor using Ganoderma Australe (FR.) pat And Trametes Menziesii (BERK.) ryvarden / Wan Razarinah Binti Wan Abdul Razak - Wan Abdul Razak, Wan Razarinah (2014)

(untitled)
The characterization of leachate from ten different landfills (sanitary and non-sanitary) in Selangor have been studied. The general chemical parameters of leachate showed large differences among the landfills. The concentration of total nitrogen, total suspended solids and ammoniacal nitrogen varied from 8.0 to 1700 mg/L, 10 to 3000 mg/L and 0.94 to 3200 mg/L, respectively. Meanwhile, the concentration of total organic carbon, biological oxygen demand (BOD5) and chemical oxygen demand (COD) were in the range of 0-45070 mg/L, 56-11360 mg/L and 165-16000 mg/L, respectively. Leachate from closed landfill had lower BOD5 and COD content but higher pH and ammoniacal nitrogen (NH3-N) content than leachate from active landfill. Therefore, higher proportion of organic materials that existed in ‘fresh’ leachates makes it biodegradable and can be removed by biological processes. Twelve different local fungal strains were screened for their capability to be used in leachate treatment. Out of twelve fungal species, two white-rot fungal species that are Ganoderma australe, and Trametes menziesii were able to grow on leachate medium. This make them the most potential to be used in bioremediation of leachate. The use of G. australe, and T. menziesii in leachate treatment was carried out using four different methods i.e. free-cell mycelia, immobilized mycelia cultures in flasks, immobilized mycelia cultures in column, and extracellular enzymes. Free-cell mycelia of G. australe and T. menziesii were capable of removing leachate BOD5 at all treatments studied. The highest BOD5 removal (89.33%) was demonstrated using G. australe in 50% unsterilized leachate. In addition, dilution of leachate and sterility of the medium did not significantly affect the percentage removal of leachate. The use of immobilized G. australe in flask displayed the best removal of BOD5 (93.09%) and COD (17.84%) for 100% leachate after 28 days of treatment compared to immobilize T. menziesii and coculture of G. australe and T. iii menziesii. Treatment of leachate by immobilized G. australe in column packing revealed small percentage of BOD5 removal which, only occurred in 100% leachate after cycle 4 (9.02%) and cycle 10 (1.43%). In contrast, COD removal in the range of 1.23-49.38% was achieved at most of the cycles where, the highest percentage (49.38%) was obtained in 50% leachate after 10th cycle. Removal of NH3-N occurred in both 50% and 100% leachate. The highest percentage of NH3-N was obtained after cycle 8 for both leachate concentration with 43.61% in 50% leachate and 38.34% in 100% leachate. Profiling of enzymes produced by G. australe and T. menziesii revealed that both fungi were able to produce ligninolytic enzymes (LiP, MnP and laccase). However, G. australe demonstrated better result in producing ligninolytic enzymes than T. menziesii. Productivity of ligninolytic enzymes by G. australe was 1.39 ± 0.60 U/ml for LiP, 45.83 ± 1.81 U/ml for MnP and 21.93 ± 0.79 U/ml for laccase while, as for T. menziesii was 3.28 ± 1.19 U/ml for LiP, 27.22 ± 0.90 U/ml for MnP and 14.04 ± 0.18 U/ml for laccase. Treatment of 100% leachate by cell-free enzymes (=crude enzymes) of immobilized G. australe at optimum crude enzymes concentration (10 U/ml) demonstrated 0.57%, 74.23% and 65.71% of BOD5, COD and NH3-N removal, respectively. Meanwhile, optimum time of exposure of crude enzymes to leachate was achieved after 4 hours exposure with 81.60% COD removal and 61.37% NH3-N removal. A promising BOD5, COD and NH3-N leachate removal was obtained with the treatment using immobilized G. australe in flask followed by treatment with crude enzymes. The percentage removal of BOD5 in leachate was 58.47% while for COD and NH3-N were 57.02% and 62.17%, respectively. This findings suggested that in order to achieve optimum removal of leachate BOD5, COD and NH3-N, combination treatment of immobilized G. australe in flask and cell-free enzymes (=crude enzymes) should be applied.